Educational Curriculum Scenario Planning in Facing Revolution 4.0 - Koento P.N. Irianto; Kristina Setyowati; Rino Ardhian Nugroho (Iapa Proceedings Conference, 2019)
Education in Indonesia is still referring to the 2013 curriculum system, where the system wants more interaction between students where students are demanded to be more active in the classroom teaching system, while the teachers only act as companions in the class. However, with the 2013 curriculum system, many students were unable to adjust the curriculum, especially the teachers also had too many teaching hours. Learning hours that are too long cause students and teachers to be more tired in the teaching and learning process. The implication is that too many study hours are charged to students so they cannot participate in activities outside of their school environment. The research in this paper will use the Systematic Literature Review research method and use a database that has been set. The results of this study will be used by researchers as a planning scenario in preparing an ideal educational curriculum and can face revolution 4.0 so that later the quality of Indonesia's next generation can be better in terms of quality education.